Factors That Influence Capital Structure With Profitability as A Moderating Variable - Wardani, Oktavia Mulyatika; Subowo, Subowo (Accounting Analysis Journal, 2020)
This study aims to determine the effect of business risk, Fixed Asset Ratio (FAR), and Time Interest Earned (TIE) on capital structure with profitability as a moderating variable. The main theories in this research are trade-off theory and signal theory. The population in this study were 155 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The sample selection used a purposive sampling technique and selected 90 companies with 235 units of analysis. The analysis techniques used descriptive statistical analysis, inferential analysis, and moderated regression analysis (MRA) which processed through IBM SPSS 23. The results show that business risk and time interest earned have a significant negative effect on the capital structure while fixed asset ratio has a significant positive effect on capital structure. Profitability is able to moderate the effect of fixed asset ratios on the capital structure but is not able to moderate the influence of business risk and time interest earned on capital structure. The conclusion of the study is that business risk has a negative effect significant to the capital structure and fixed asset ratio has significant positive effects on capital structure. This can be used as the basis that companies must be careful when raising external funds because it can affect the efficiency and profitability of the company.